The development of ontological model for clinical decision support system: A case study of triage of pediatric hip pain in the emergency department - Wen, Hongyang (University of Ottawa (Canada), 2006)
Clinical Decision Support Systems (CDSS), for providing patient specific advice, can only be accepted in clinical practice if they can fit in a clinician workflow. This would require such a CDSS to have diversified support capabilities, to be mobile, and to have flexible functionality. Such a system can be designed and developed only in a modular fashion where the high level abstractions describe the logic among different system components. Ontology, which is a formal specification of shared conceptualization, can be used to create a high level abstraction. Such decoupling of abstract CDSS logic from low level implementation facilitates developing and adding new applications and increases the reusability of different system components. In this research it is argued that a developed CDSS, according to ontology driven design with the ontological model of a problem domain expanded by a clinical decision support requirements, allows the creation of a system that is aligned with clinical workflow. In this research the proposed approach is illustrated with the CDSS for triaging pediatric hip pain (HP) in the Emergency Department. This application (called MET-HP) is created within the MET (Mobile Emergency Triage) environment that implements the ontology driven design principles. MET-HP is a mobile CDSS that includes a decision model derived from the analysis of retrospective chart data and it facilitates early triage of a child using incomplete data. Keywords. Ontology; ontological model; ontology driven design; ontological engineering; clinical decision support system; data mining; knowledge model; knowledge based system.
Keywords: Health Sciences, Health Care Management.; Engineering, System Science.